Dydaktyka literatury w latach 1918-1939. Metodologiczne założenia badań = The history of didactics of polish literature in the pre-war Poland. Several methodological hypotheses - Marchewa, Janusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper is an attempt to prove that it is imposible to develop science without advances in methodology. The author tried to adopt the latest achievements in the theoray of historical knowledge for the needs of history of teaching and learning Polish literature. Having made use of the scientific publications by W. Pasterniak, J. Topolski, J. Kmita, F. Grucza, the author put forward several methodological hypotheses of research in the history of teaching and literature. These hypotheses first of all deal with the theory of source knowledge, the definitig of notions and the principles of the reconstructions of the didactic process. The paper constitutes an introduction to systematic research in the history of dydactics of Polish literature in the pre-war Poland.
Keywords: dydaktyka literatury; metodologia; badania; dwudziestolecie międzywojenne